Madrasah Diniyah Alwaliyah dalam Meningkatkan Mutu Pendidikan Islam di Desa Hadundung Selama Pandemi Covid-19 - Muhammad Arif (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2021)
This article aims to look at the role of Madrasah Diniyah Awaliyah in improving the quality of Islamic education in Hadundung village during the Covid-19 pandemic. Islamic education is a means to prepare Muslims to understand Islam. The research method used is descriptive qualitative. The data in this study were sourced from primary data and secondary data. The existence of Madrasah Diniyah Awaliyah during the current pandemic helps parents in educating their children because only Madrasah Diniyah Awaliyah is conducting an active teaching and learning process. The results of the study found that there was still a shortage of Islamic education because the last few years MDA was closed due to government policies and had only been reopened for 6 months. So that many students are less interested in learning and forget the lessons that have been taught.